Search for Doubly Charged Higgs Boson Pair Production in the Decay to μ+μ+μ-μin pp̄ Collisions at √s = 1.96 TeV - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, D. L.; Adams, M.; Adams, T.; Agelou, M.; Agram, J. L.; Ahmed, S. N.; Ahn, S. H.; Alexeev, G. D.; et al. (American Physical Society (APS), 2004)
The pair production of doubly charged Higgs bosons in the decay to μ+ μ+ μ- μ- in pp̄ Collisions was investigated. It was observed that the total signal efficiency for the event selection was (47.5±2.5)% and does not depend on the mass of the doubly charged Higgs boson in the studied mass range. Data and the Monte Carlo simulation, for both the normalization and shapes of the dimuon mass and δφ distributions were found to be in agreement. A lower limit of 118.4 GeV/c2 for a left-handed and 98.2 GeV/c2 for a right-handed doubly charged Higgs boson, was obtained, by taking into account systematic uncertainties.